UBSTITUTION OF UREA FERTILIZER WITH BIO-SLURRY FERTILIZER ON THE GROWTH AND PRODUCTION OF Stenotaphrum secundatum - S. S., Sri Wahyuni; Budiasa, I K. M.; Suarna, I W. (Jurnal Peternakan Tropika, 2018)
The efforts to increase grass production can be done with effective fertilization but not negative impact to the environment. Substitution of inorganic fertilizer with organic fertilizer is one effort that can be done to maintain the physical, chemical and biological soilcharacteristics.This experiment aims to determine the effect of urea fertilizer substitution with bio-slurry fertilizer on the growth and production of Stenotaphrum secundatum grass.The experiment was conducted at Greenhouse, Research Station of Faculty of Animal Husbandry, Udayana University, Denpasar for 12 weeks. The design used was completely randomized design (CRD) with five combined treatments and five replications so that there were 25 pots of experimental unit. Combination treatmentconsists of B 0 : without bio-slurry fertilizer and urea fertilizer 300 kg/ha, B 5 : bio-slurry fertilizer 5 tons/ha and 250 kg/ha urea, B 10 : bio-slurry 10 tons/ha and 200 kg/ha urea, B 15 : bio-slurry fertilizer 15 tons/ha and 150 kg/ha urea, B 20 : bio-slurry fertilizer 20 tons/ha without urea fertilizer.Variables observed were growth, production and growth characteristics.The results showed that the substitution of urea fertilizer with bio-slurry fertilizer was significantly different (P <0.05) in variables of leaf number, number of branches, root length, leaf dry weight, dry weight of stem, total dry weight of forage, leaf dry weight ratio with dry weight of stem, leaf area and not significantly different (P>0.05) on variable length of segment, length of segment, number of tiller, root dry weight, root volume, top root ratio and chlorophyll content.Based on the research result, it can be concluded that the substitution of urea fertilizer 50% (150 kg / ha urea with 15 ton/ha bio-slurry ) resulted in growth and production of Stenotaphrum secundatum grass which is not different from 100% urea fertilizer (300 kg / ha) Keywords:Fertilizer Substitution, Bio-Slurry, Growth,Production, Stenotaphrum secundatum